Analysis of The Effect of Education Level on Labor Absorption in Mamuju District, Indonesia - Taombe, Irwan; Halim, Abdul; Arsyad, Muhammad (Golden Ratio of Social Science and Education, 2024)
This study aims to analyze the effect of education level on labor absorption in Mamuju Regency during the 2014-2023 period. The data used in this study consists of time series data on the number of labor forces absorbed, categorized by education level: elementary school, junior high school, high school, and university. The data analysis was conducted using the multiple linear regression method to test the effect of each education variable on labor absorption. The results reveal that none of the education level variables have a significant influence on labor absorption, either partially or simultaneously. These findings suggest that labor absorption in Mamuju Regency is influenced more by factors other than formal education, such as practical skills and local labor market demands. This underscores the need for economic diversification and the development of relevant skills training programs to enhance the competitiveness of the local workforce.